Art-making with refugees and survivors : creative and transformative responses to trauma after natural disasters, war and other crises - Jones, Sally Adnams (Jessica Kingsley Publishers, 2018)
This timely book reveals the therapeutic effect group art projects can have when working with survivors and refugees of war, natural disaster, poverty, pandemic and genocide. Artists and therapists who have worked with trauma internationally explain the theory and practice of their approaches and provide inspiration for others working in this area.